The role of intrinsically disordered C‐terminal region of FliK in substrate specificity switching of the bacterial flagellar type III export apparatus. Issue 4 (15th June 2017) - Kinoshita, Miki; Aizawa, Shin‐Ichi; Inoue, Yumi; Namba, Keiichi; Minamino, Tohru
Summary: The bacterial flagellar export switching machinery consists of a ruler protein, FliK, and an export switch protein, FlhB and switches substrate specificity of the flagellar type III export apparatus upon completion of hook assembly. An interaction between the C‐terminal domain of FliK (FliKC ) and the C‐terminal cytoplasmic domain of FlhB (FlhBC ) is postulated to be responsible for this switch. FliKC has a compactly folded domain termed FliKT3S4 (residues 268–352) and an intrinsically disordered region composed of the last 53 residues, FliKCT (residues 353–405). Residues 301–350 of FliKT3S4 and the last five residues of FliKCT are critical for the switching function of FliK. FliKCT is postulated to regulate the interaction of FliKT3S4 with FlhBC, but it remains unknown how. Here we report the role of FliKCT in the export switching mechanism. Systematic deletion analyses of FliKCT revealed that residues of 351–370 are responsible for efficient switching of substrate specificity of the export apparatus. Suppressor mutant analyses showed that FliKCT coordinates FliKT3S4 action with the switching. Site‐directed photo‐cross‐linking experiments showed that Val‐302 and Ile‐304 in the hydrophobic core of FliKT3S4 bind to FlhBC . We propose that FliKCT may induce conformational rearrangements of FliKT3S4 to bind to FlhBC . Abstract : FliK and FlhB induce the switching of substrate specificity of the bacterial flagellar type III export apparatus upon completion of the hook structure. Genetic analyses and photo‐cross‐linking experiments provide evidence suggesting that conformational rearrangements of the C‐terminal domain of FliK are required for the interaction with FlhB.